The psychology of flavour - Stevenson, Richard J. (Oxford : Oxford University Press, 2009)
Flavour is arguably the most fascinating aspect of eating and drinking. It utilises a complex variety of senses and processes that incredibly work together to generate a unified, and hopefully pleasurable, experience. This text explores and describes what we know about the psychology and biology of flavour.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Flavor; Senses and sensation